Ontology, Methodological Individualism, and the Foundations of the Social Sciences - Sugden, Robert (Journal of Economic Literature, 2016)
This is a review essay based on a critical assessment of The Ant Trap: Rebuilding the Foundations of the Social Sciences by Brian Epstein. Epstein argues that models in the social sciences are inadequate because they are based on a false ontology of methodological individualism, and proposes a new model of social ontology. I examine this model and point to flaws in it. More generally, I argue against Epstein's methodological approach, which treats social ontology as prior to social scientific modeling and as certifying the “building blocks” that modelers then use. I argue that modelers can legitimately shape the building blocks for their own models.